Pemetaan Karakteristik Penjualan Minyak Goreng di Indonesia dengan Analisis Biplot: Studi pada Sepuluh Merek Populer 2021-2022 - Supriadi, Cecep; Hertina, Dede (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Cooking oil is a staple food product frequently used by Indonesian households. According to data from the Central Bureau of Statistics (2022), 90.27% of households used cooking oil during the 2019-2021 period, with an average expenditure of 1.35% of total monthly expenses. This study analyzes the sales and characteristics of ten popular cooking oil brands in Indonesia in 2021-2022, namely Fortune, Minyakita, Sania, Bimoli, Sunco, Sovia, Tropical, Hemart, Sabrina, and Filma, using biplot analysis to understand consumer behavior and market competition. The study finds that the Fortune brand has high market penetration and expenditure per buyer, whereas the Filma brand shows a high volume of purchases per transaction. Biplot analysis reveals the proximity of characteristics among brands such as Sania, Tropical, Sunco, and Bimoli, while Fortune stands alone in its sales characteristics. The study also identifies that sales metrics like penetration, expenditure per buyer, and average purchase frequency play important roles in understanding consumer preferences and the market positioning of brands. These results provide deep insights into effective marketing strategies to enhance the sales and competitiveness of cooking oil brands in Indonesia.